TRANSPARENCY CONTRADICTION OF PUBLIC INFORMATION BETWEEN THE ACEHNESE GOVERNMENT OFFICER OF INFORMATION-DOCUMENTATION WITH AN INDICATION OF CORRUPTION IN ACEH - Ashabul Chairi; Ubaidullah Ubaidullah (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
The right of citizens to obtain information has been regulated in article 3 of Decree number 14, 2008 on Public Information Openness. The mandate of Law no. 14 of 2008 has been well implemented by the Aceh government by establishing the Main Information and Documentation Management Officer (PPID) of Aceh. The problem is Aceh through PPID Mainly has gained the best achievement in national level transparency category of public information but the level of indication of corruption is also high in Aceh. The better the level of transparency of public information of a region, the lower the number of corruption.The writing of this thesis aims to explain the performance of Aceh's main PPID in obtaining the best achievement at national level and to explain the relationship between transparency of public information of Aceh PPID with indication of corruption in Aceh. This study uses descriptive qualitative methods and the data collection was conducted through interview and library research.The results of the study show that the main PPID of Aceh is the preparation of Standard Operating Procedure (SOP), building the official website, coordinating and coaching for PPID assistant in related offices, and compiling public information list both in PPID Utama Aceh and also accompaniment in PPID helpers. The transparency of public information only works well in Aceh's main PPID, but not in the Aceh government as a whole.The conclusion is that the performance of PPID Utama Aceh has been maximal or good in implementing Decree number 14, 2008 so as to obtain the best performance at the national level. Achievement of transparency of public information acquired by Aceh's main PPID does not affect or can not suppress high levels of corruption indication in Aceh.Keywords: Good Governance, Transparency of Public Information, Corruption